Corrosion and microstructure studies on magnesium alloy composite reinforced with mSiCp fabricated via powder metallurgy. (2023) - Velavan, K.; Palanikumar, K.; Dhanush, V.; Rajapandiyan, S.; Thamesh Kumar, U.; Aishwarya, M.
Highlights: A novel micron sized SiC reinforced AZ61 magnesium alloy was fabricated through powder metallurgy route. Corrosion performance of the fabricated magnesium matrix composite was evaluated using Electrochemical Impedance Spectroscopy technique. Addition of SiC particulates increases the corrosion resistance of the magneisum composite. Uniform distribution of SiC is possible with powder metallurgy and it enhances the corrosion resistivity. Abstract: In this work, the influence of adding different weight fractions (0, 5, 10 and 15%) of micron-sized silicon carbide (SiC) particles reinforced in AZ61 magnesium alloy is studied by identifying their microstructures and their corrosion behaviour. It is common knowledge that magnesium has poor corrosion resistance properties, in order to improve its strength and corrosion behaviour, hard reinforcements are included to form composites. Powder metallurgy route is adopted for fabricating the said magnesium metal matrix composite (MMMCs) by blending, mixing, compacting and sintering the desired quantity of powders in a controlled environment to avoid oxidation. Optical and Scanning electron microscope (SEM) images are captured to identify the distribution of reinforced SiC particles in AZ61 matrix. Corrosion studies are performed based on Electrochemical Impedance Spectroscopy (EIS) tests as per ASTM G106 procedure. Optical micrographs show uniform distribution of ceramic particulates in the matrix of AZ31. Corrosion resistance increases with higher weight fractions of SiC.